Competitiveness of the Chinese Economy and Its Link to the Global Energy Prices Development - Baláž, Peter; Harvánek, Lukáš (International Journal of Energy Economics and Policy, 2016)
The article analyses the relationship between competitiveness of the Chinese economy and the prices of energy resources. Based on theoretical framework of the most important economists and international organizations in the field of research, the authors analyze statistical data concerning Chinese competitiveness embodied in Real Effective Exchange Rate (REER) and oil, natural gas and coal global prices using basic correlation and regression analysis and advanced quantitative methods (Granger causality test, cointegration analysis). Secondly, the authors choose the Producer Prices Index (PPI) as next indicator of competitiveness of the Chinese producers, as the one of the key inputs determining final selling prices are prices of energy carriers. By comparing these two indicators to global energy prices reflected by indexes or in real prices, the authors analyse to what extent these indicators affect each other and what are the ultimate implications for competitiveness of the Chinese economy. Keywords: Chinese economy, competitiveness, energy resources, energy prices JEL Classifications: F110, F14, F15